STRATEGI KOMUNIKASI BISNIS DI KAMPUNG WISATA BISNIS TEGALWARU CIAMPEA KABUPATEN BOGOR - Sheylla Ayu Prahasty; Diana Amaliasari; Qoute Nuraini C (Jurnal Penelitian Sosial Ilmu Komunikasi, 2019)
AbstractThe study aims to know the communication strategy business that is applied by Kampung Wisata Bisnis Tegalwaru and  review the strategy of  the long run it will be carried out in the face of the licensing related to the implementation of the communication strategy business. The metode of researches is descriptive qualitatif method, in obtaining data using the method of indepth interviews, observations, documentation, and the study of the library. The result showed that in making the communication strategy business, Kampung Wisata Bisnis Tegalwaru make a long-term plan called Renstra (Rencana Strategis) the community empowerment. The obstacles or factors inhibiting the way the process of communication strategy to the business in Kampung Wisata Bisnis Tegalwaru is: Lack of facilities and infrastucture to accomodate visitors in large numbers, the lack of coordination in the team, as well as lisencing Kampung Wisata Bisnis Tegalwaru as a tourist village that hasnt been registered in the Departement of Culture and Tourism of Bogor Regency. Keywords: Strategy, Communication Strategy Business, Kampung Wisata Bisnis Tegalwaru